SCIENTIFIC AND METHODICAL APPROACH TO THE PLACE DETERMINATION OF FOREIGN CURRENCY EXCHANGE REGULATION IN THE SYSTEM OF STATE ECONOMIC POLICY OF UKRAINE - Журавка , Федір (Socio-economic relations in the digital society, 2019)
The article is devoted to the substantiation and development of theoretical and methodological bases of currency regulation and currency control system in order to defi ne its’ role and place in the state economic regulation system of Ukraine. On the basis of scientifi c analysis the author’s defi nition of «currency regulation» concept is offered. Besides, the peculiarities of the Ukrainian currency regulation system are investigated. It is proved that currency regulation is characterized not only as an element of the monetary policy but also as an integral part of the whole system of economic policy instruments of Ukraine.